A política municipal de habitação na cidade de Santos – SP na década de 1990 - Braga, Rosana Aló Maluza (2004)
This paper aims to show the governmental action on the Housing Municipal Policy implementation on the 1990´s within Santos City, São Paulo State. To do so, it was made a research about the Federal Housing Policy on the BHN period and also on the posterior period till 2000 in order to verify the trajectory of the federal policy on the housing field. The Municipal Housing Policy conquered special importance after the promulgation of the 1988 Constitution when the Federal Government gave to the municipalities the responsibility for their own urban policies. Within this research, we aim to present the factors that influenced the formulation and implementation process and the results of such policy in this period. We presented this policy content on three distinct administrations associated with the instruments which made the implementation possible: The ZEIS law – Special Zones for Social Interest, the FINCOHAP – Popular Housing Construction Incentive Fun, Municipal Housing Council and the Municipal Housing Conferences. This choice for Santos City is due to the master student has been a participant person on the Santos Housing Policy process. The used methodology was based on gaining information through out the hypotheses made for this research. It has been verified, with this study, that Federal Government on the BNH age had the same housing policy for many Brazilian cities, not considering the specificities of each one, conceiving resources for housing constructions. On the post 1988 Constitution period, the municipalities began an autonomy process of their urban politics. On the Housing field, the Federal Government gave the responsibility for the federative institutions in order to formulate their policies without conceiving resources. Generalizing, so these new policies let the cities economically dependent on the Federal Government which don’t have federal channel to redirect resources like for Health and Education, making impossible the municipality to supply its housing deficit by their own.